The Structure of The Electrode Material Based on NI(OH)2/C Composite for Energy Storage Devices - Khemiy, O.; Yablon, L.; Budzulyak, I.; Morushko, O. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The paper presents the results of studies of the structure β -Ni(OH)2/C composite. It is shown that the XRD-pattern of heated composite β -Ni(OH)2 /C has a broad diffraction peak at 23°, which can be attributed to the activated carbon in addition to peaks characteristic for NiO